Playfulness from children’s perspectives: development and validation of the Children’s Playfulness Scale as a self-report instrument for children from 3 years of age - Duss, Isabelle; Rüdisüli, Cornelia; Wustmann Seiler, Corina; Lannen, Patricia (Frontiers in Psychology, 2023)
Children's playfulness refers to children's enjoyment, motivation, and engagement in play and has been predominantly assessed from an adult perspective. To assess children's perspectives on their own playfulness, we adapted and modified the Children's Playfulness Scale (CPS) for children from 3 years and used a two-level response format with a total of four answer options. We tested the self-report scale with 564 children between 3 and 8 years of age who attended childcare center or kindergarten. Results indicated that the adapted version of the CPS identified the five distinct domains of playfulness: social spontaneity, cognitive spontaneity, physical spontaneity, sense of humor, and manifest joy; however, results showed invariance across multiple groups for gender, age, and language skills. A highly significant positive correlation was found between children's self-reported playfulness and children's self-reported social self-concept (r = .54, p < .001), which demonstrates convergent validity. No association was found with teacher proxy report of children's playfulness (r = .03, p = .92). Overall, our study confirmed first indications of the validity of the modified CPS as a reliable instrument for assessing children's self-reported playfulness. This enables children as young as 3 years old to be assessed on their own playfulness, which is a valuable supplement to the adult perspective.